PENGUKURAN EFEKTIVITAS PEMASARAN TAGLINE IKLAN SHOPEE DALAM MELIHAT MINAT KONSUMEN - Arafah, santu (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2019)
The tagline of the ad is a powerful marketing tool to motivate customers support a brand. The tagline of the ad utilized to make the buyer always remember with catchprasenya products. The tagline can create new image against a brandnya and persuasive effect to the community. In this case the ad tagline shopee that reads